In Vitro Micropropagation of Jatropha curcas L. from Bud Aggregates - Medza Mve, Samson Daudet; Mergeai, Guy; Druart, Philippe; Baudoin, Jean Pierre; Toussaint, André (Journal of Technology Innovations in Renewable Energy, 2013)
Entire plants were regenerated from nodes explants of Jatropha curcas L. following a procedure of bud aggregate induction on MS (Murashige and Skoog) medium supplemented with 25 mg.l-1 citric acid, 12.2 mg.l-1 adenine sulfate, 15 mg.l-1 L-arginine, 2.46 µM IBA (indole-3-butyric acid), 30 g.l-1 sucrose and 7 g.l-1 of agar, and enriched with different balances of BA (benzyladenine) and L-glutamine. The histological studies performed on aggregates showed that the buds result from both the development of axillary buds and adventitious budding starting from underlying tissues of the explant. The culture medium containing 6.65 µM BA and 25 mg.l‑1 L-glutamine gave the best results with an average of 64 buds per aggregate after three weeks for all accessions tested. The buds developed into shoots when placed in an MS medium supplemented with 2.21 µM BA, 5.70 µM IAA (indole-3-acetic acid) and 15 mg.l-1 L‑arginine. These shoots were isolated and then rooted in MS containing 2.46 µM of IBA, 2% sucrose and 0.7% agar. The entire process took 13 weeks with a 98% survival rate in terms of plantlets acclimatization. We obtained a multiplication rate of 13 buds per explant and per subculture which is the double of those obtained in other recent works based on the micropropagation of J. curcas from node explants. This protocol is economically more profitable.